2023
DOI: 10.1007/s10943-023-01763-1
|View full text |Cite
|
Sign up to set email alerts
|

Libyan Healthcare Professionals’, Patients’ and Caregivers’ Perceptions and Religious Beliefs about Cancer Pain and its Management: A Descriptive Qualitative Study

Abstract: Cancer pain remains a significant problem worldwide. It is often undertreated and presents in about half of cancer patients. Although several guidelines and pharmacological interventions for cancer pain management (CPM) exist, inadequate assessment and undertreatment of cancer pain are well-documented globally, especially in developing countries, including Libya. Perceptions, cultural and religious beliefs of healthcare professionals (HCP), patients, and caregivers about cancer pain and opioids are reported as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“… Javier et al (2016) concurred that a lack of available guidelines was one of the institution-related barriers to cancer pain management. A study by Makhlouf et al (2023) also confirmed that healthcare providers perceived the absence of policies, guidelines, education and training in managing pain as a barrier to cancer pain management. This study confirmed that limited medications were available to manage cancer pain.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“… Javier et al (2016) concurred that a lack of available guidelines was one of the institution-related barriers to cancer pain management. A study by Makhlouf et al (2023) also confirmed that healthcare providers perceived the absence of policies, guidelines, education and training in managing pain as a barrier to cancer pain management. This study confirmed that limited medications were available to manage cancer pain.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, two beliefs affecting adherence to cancer pain management regimens and follow-up included the belief that witchcraft was responsible for their cancer, and male patients not reporting pain due to the belief that this reflects weakness. Makhlouf et al (2023) and Uysal (2018) also reported cultural beliefs as barriers to cancer pain management. In a study by Kwon (2014) , negative attitudes toward morphine was reported, due to the fear of addiction, religious concerns, and cultural prohibitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation